Exponential Relationship Between Maximal Apnea Duration and Exercise Intensity in Non-apnea Trained Individuals - Guimard, Alexandre; Joulia, Fabrice; Prieur, Fabrice; Poszalczyk, Gauthier; Helme, Kader; Lhuissier, François J. (Frontiers in Physiology, 2022)
It is well known that the duration of apnea is longer in static than in dynamic conditions, but the exercise intensity impact on the apnea duration need to be investigate. The aim of this study was to determine the apnea duration/exercise intensity relationship and the associated metabolic parameters. Ten healthy active young men non-trained in apnea (NAT) participated to this study. During a first visit they carried out a maximum static apnea (SA) and a maximal progressive cycle exercise to evaluate the power output achieved at peak oxygen uptake (PVO2peak). During a second visit, they performed four randomized dynamic apneas (DA) at 20, 30, 40 and 50% of PVO2peak (P20, P30, P40 and P50) preceded by 4 minutes of exercise without apnea. Duration of apnea, heart rate (HR), arterial oxygen saturation (SpO2), blood lactate concentration, rating of perceived exertion (RPE) and subjective feeling were recorded. Apnea duration was significantly higher during SA (68.1 ± 23.6 s) compared to DA. Apnea duration at P20 (35.6 ± 11.7 s) was higher compared to P30 (25.6 ± 6.3 s), P40 (19.2 ± 6.7 s) and P50 (16.9 ± 2.5 s). Apnea duration/exercise intensity relationship followed an exponential function (y = 56.388e-0.025x). SA as DA performed at P20 and P30 induce a bradycardia. Apnea induces a SpO2 decrease which is higher during DA (-10%) compared to SA (-4.4%). The decreases of SPO2 recorded during DA don’t differ despite the exercise intensity increase. An increase of blood lactate concentration [La] was observed in P30 et P40 conditions. RPE and subjective feeling were unchanged whatever apnea conditions. These results suggest performed DA at 30% of VO2peak could be the best compromise between apnea duration and exercise intensity. Then, DA training at low intensity could be added to aerobic training since despite the moderate hypoxia it’s sufficient to induce and increase of [La] generally observed during high intensity training.